The refill gap: clean cooking fuel adoption in rural India. (29th December 2020) - Cabiyo, Bodie; Ray, Isha; Levine, David I
Abstract: From 2016 to 2019, the Indian Pradhan Mantri Ujjwala Yojana (PMUY) distributed over 80 million liquefied petroleum gas (LPG) stoves, making it the largest clean cooking program ever. Yet, evidence shows widespread continued use of the traditional chulha, negating the potential health benefits of LPG. Here we use semi-structured interviews with female and male adults to understand the drivers of LPG usage in Mulbagal, Karnataka, the site of a proto-PMUY program. We find that respondents perceive the main value of LPG to be saving time, rather than better health. We also find that norms of low female power in the household, in addition to costs, delay saving for and ordering LPG cylinder refills. Namely, female cooks controlled neither the money nor the mobile phone required to order a timely refill. These factors together contribute to the 'refill gap': the period of non-use between refilling cylinders, which may range from days to even months. Our work reveals how gender norms can amplify affordability challenges in low-income households.